AUTOMATED INFORMATION SYSTEM OF CONTROL OF AVAILABILITY AND USING OF NATURAL RESOURCES - V. A. Rybak; A. Shokr (Системный анализ и прикладная информатика, 2017)
The purpose of this work is to create an automated system for recording the availability and use of natural resources in the Republic of Belarus. To achieve this goal, the following main tasks were solved: to conduct an analytical review of similar information systems, to highlight their advantages and disadvantages, to develop a new improved version of the system, taking into account previous experience of use, to test the received tool for assessing the environmental friendliness of nature-intensive production and technology. The article provides an analytical review of modern software tools for automation of accounting and rational use of natural resources. It is shown that their application is not possible for a qualitative solution of urgent problems in our country. Three versions of the automated system designed for collecting, storing, processing and presenting subject data on the availability and use of natural resources are consistently described. Comparative analysis with existing analogs is carried out. The distinctive features and advantages of the proposed solution are indicated. With the use of the developed system, the nature of projects in the State Program for Innovative Development of the Republic of Belarus for 20011–2015 was evaluated. The Ministry of Energy is pointed as the state customer of the most resource-intensive use projects and  technologies. Thus, it is shown that the proposed automated information system for recording the availability and use of natural resources makes it possible to collect, store, analyze and display the subject information, and is an actual basis for supporting the adoption of management decisions in the field of natural recourses management and environmental protection. The obtained results were used by the State Committee for Science and Technology for the evaluation of projects as part of the State Program of Innovative Development of the Republic of Belarus for 2011–2015 for the sake of natural recourses cost-effectiveness.